Isolation, characterization, and genomic analysis of a novel bacteriophage MA9V-1 infecting Chryseobacterium indologenes: a pathogen of Panax notoginseng root rot - Zou, He; Ding, Yafang; Shang, Junjie; Ma, Chunlan; Li, Jinhua; Yang, Ye; Cui, Xiuming; Zhang, Jinhao; Ji, Guanghai; Wei, Yunlin (Frontiers in Microbiology, 2023)
Chryseobacterium indologenes is one of the primary causative agents of root rot of Panax notoginseng, which significantly affected plant growth and caused economic losses. With the increasing incidence of antibiotic-resistant bacterial phytopathogens, phage therapy has been garnered renewed attention in treating pathogenic bacteria. However, the therapeutic potential of phage therapy on root rot of P. notoginseng has not been evaluated. In this study, we isolated a novel lytic phage MA9V-1 infecting C. indologenes MA9 from sewage and monitored the formation of clear and round plaques with a diameter of approximately 0.5–1.5 mm. Phage MA9V-1 exhibited rapid absorption (>75% in 8 min), a latency period of 20 min, and a burst size of 10 particles per cell. Transmission electron microscopy indicated that the phage MA9V-1 is a new myovirus hosting C. indologenes MA9. Sequencing of phage genomes revealed that phage MA9V-1 contained a linear double-stranded DNA genome of 213,507 bp with 263 predicted open reading frames, including phage structure, host lysing, and DNA polymerase/helicase but no genes of tRNA, virulence, and antibiotic resistance. Our proteomic tree and genomic analysis revealed that phage MA9V-1 shares identity with Sphingomonas phage PAU and Tenacibaculum phage PTm1; however, they also showed apparent differences. Further systemic evaluation using phage therapy experiments on P. notoginseng suggested that phage MA9V-1 can be a potential candidate for effectively controlling C. indologenes MA9 infection. Thus, we have presented a novel approach to solving root rot in P. notoginseng.